2021
DOI: 10.1080/09658211.2021.1910311
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of intrusive mental images in clinical disorders: what can “non-veridical” images tell us about the nature of human memory?

Abstract: Intrusive mental images associated with autobiographical memories or depicting imagined scenes are common in psychological disorders. Although there is a growing body of literature on their contribution to psychopathology and their role in therapy, to date there have been limited attempts to categorise the different types of images that patients experience. In this article, we present a taxonomy which ranges from veridical to non-veridical intrusive images.We highlight the fact that many types of images consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…It is suggested that memories of multiple experiences are integrated in FF’s, including experiences in other settings than speech situations, or, although not assessed in our study, fantasy-based simulations ( Rachman, 1977 ; Dadds et al, 1997 ). However, it remains difficult to reliably assess to what extent future-oriented FF images are fantasy-based versus veridical ( Çili and Stopa, 2021 ), and thus, to categorize these FF images in SA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that memories of multiple experiences are integrated in FF’s, including experiences in other settings than speech situations, or, although not assessed in our study, fantasy-based simulations ( Rachman, 1977 ; Dadds et al, 1997 ). However, it remains difficult to reliably assess to what extent future-oriented FF images are fantasy-based versus veridical ( Çili and Stopa, 2021 ), and thus, to categorize these FF images in SA.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined to what extent FF images are experienced in (impending) speech situations in SA, and whether FF images are characterized as being vivid, distressing, accompanied by negative feelings, and seen from an observer perspective. Also, we examined the similarity of FF imagery to associated memories to further explore how to categorize these images ( Çili and Stopa, 2021 ). Imagined catastrophes that might currently elicit anxiety and avoidance behaviors in SA, may be based on or linked to memories of past fearful events, as was also found in studies with broad assessments of negative imagery in social anxiety ( Hackmann et al, 2000 ; Moscovitch et al, 2011 ; Schreiber and Steil, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although intrusive images can represent memories, that is not always the case (Krans et al, 2015). Intrusive images can additionally represent, e.g., current (negative) self-images, hypothetical reconstructions, flash forwards, and images of feared outcomes (Çili & Stopa, 2021;Kadriu et al, 2019;Krans et al, 2015). No study so far has compared the number of intrusive images that represent memories and non-memories in patients with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intrusive images do not necessarily contain content that corresponds fully to an earlier memory. However intrusive images may still be associated conceptually with memories that share the same meaning or emotional tone (Çili & Stopa, 2021). For example, someone with intrusive images of themselves looking "fat", may emotionally associate this image with the memory of being rejected by a potential partner because of their weight.…”
Section: Introductionmentioning
confidence: 99%